THE MELTDOWN - Kinney, Jeff; Smith, Deborah, 1987-; Feng, Lisk (New York : Amulet Books, 2020)
When snow closes Greg Heffley's middle school, he and his best friend, Rowley Jefferson, face a fight for survival as warring gangs turn the neighborhood into a wintry battlefield.
Translated from the Korean.
Keywords: Heffley, Greg -- Juvenile fiction; Snow -- Juvenile fiction; Best friends -- Juvenile fiction; Winter -- Juvenile fiction